Identification of extracellular matrix-related biomarkers in colon adenocarcinoma by bioinformatics and experimental validation - Yin, Yongkui; Yang, Xiaojie; Cheng, Zhengyi; Wang, Hui; Lei, Jun; Wang, Dan; Wang, Peiwen; Li, Biao; Mi, Jing; Yuan, Qi (Frontiers in Immunology, 2024)
Backgrounds: Extracellular matrix (ECM) is an important component of tumor microenvironment, and its abnormal expression promotes tumor formation, progression and metastasis. Methods: Weighted gene co-expression network analysis (WGCNA) was used to identify ECMrelated hub genes based on The Cancer Genome Atlas (TCGA) colon adenocarcinoma (COAD) data. COAD clinical samples were used to verify the expression of potential biomarkers in tumor tissues, and siRNA was used to explore the role of potential biomarkers in cell proliferation and epithelial-mesenchymal transition (EMT). Results: Three potential biomarkers (LEP, NGF and PCOLCE2) related to prognosis of COAD patients were identified and used to construct ERGPI. Immunohistochemical analysis of clinical samples showed that the three potential biomarkers were highly expressed in tumor tissues of COAD patients. Knockdown of LEP, NGF or PCOLCE2 inhibited COAD cell proliferation and EMT. Dictamnine inhibited tumor cell growth by binding to these three potential biomarkers based on molecular docking and transplanted tumor model.The three biomarkers can provide new ideas for the diagnosis and targeted therapy of COAD patients.